The Intersection of IgE Autoantibodies and Eosinophilia in the Pathogenesis of Bullous Pemphigoid - Messingham, Kelly N.; Crowe, Tyler P.; Fairley, Janet A. (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is an autoimmune blistering disease characterized by autoantibodies targeting cellular adhesion molecules. While IgE autoantibodies are occasionally reported in other autoimmune blistering diseases, BP is unique in that the majority of BP patients develop an IgE autoantibody response. It is not known why BP patients develop self-reactive IgE and the precise role of IgE in BP pathogenesis is not fully understood. However, clinical evidence suggests an association between elevated IgE antibodies and eosinophilia in BP patients. Eosinophils are multipotent effector cells involved in cytotoxicity and immune modulation and both clinical and experimental studies indicate that activated eosinophils play a role in the development of BP lesions. The putative interaction between IgE and eosinophils is a primary focus in current studies aimed at understanding the key components of disease pathogenesis. In this review, we provide an overview of BP pathogenesis, highlighting clinical and experimental evidence supporting central roles for IgE and eosinophils. Additionally, therapeutics targeting IgE, the Th2 axis, or eosinophils are also discussed.